Column reverse rougher flotation of iron bearing fine tailings assisted by HIC and a new cationic collector. (1st September 2020) - Araujo, V.A.; Lima, N.; Azevedo, A.; Bicalho, L.; Rubio, J.
Highlights: Reverse rougher column flotation of iron ore tailings to get iron and siliceous concentrates. An amide-amine cationic collector was utilised without starch as depressant. High intensity conditioning was necessary for a good flotation of siliceous ultrafines. Process efficiency depended on maximizing the operating superficial flow parameters. Three-products column (3PC) was successful in producing rich siliceous concentrates (<10% Fe). Abstract: This work focuses on a novel treatment process for Brazilian iron bearing fine tailings by rougher reverse column flotation assisted by high-intensity conditioning (HIC) with a new cationic collector in a conventional column cell (CCC) and in a modified three-product column (3PC). The samples (30–35% solids), corresponded to very fine (49% of the mass below 10 µm) and low-grade iron bearing tailings (40–43% Fe) collected from the thickened overflow of the desliming hydrocyclones. The objectives were to obtain two "concentrates" as feeds to future beneficiation processes; first, a non-floated product with a minimum grade about 48–50% Fe content (iron concentrate) and the floated material with a maximum grade of 15% Fe (named siliceous concentrates). Both goals were achieved due to the high selectivity of a chemical composite of amide-amines acting as a flotation collector/frother for the siliceous gangue particles. In addition, HIC was needed to enhance the flotation recoveries by improving capture by bubbles; without HIC, the mass being floated was very low (<10%). Best results were obtained by optimising the superficial flux parameters (Jsl, Jg and Jw) and residence time. Flotation in the 3PC led to purer siliceous concentrates with Fe grade lower than 10–12% Fe. Mechanisms involved were discussed in terms of mass transfer and interfacial phenomena. It is believed that the process has a high potential in the treatment of fresh iron tailings, a very old and relevant problem in the area.